2003
DOI: 10.4141/p02-031
|View full text |Cite
|
Sign up to set email alerts
|

Dwarf sunflower response to row spacing, stand reduction, and defoliation at different growth stages

Abstract: Johnson, B. L. 2003. Dwarf sunflower response to row spacing, stand reduction, and defoliation at different growth stages.Can. J. Plant Sci. 83: 319-326. Growth compensation of dwarf sunflower (Helianthus annuus L.) hybrids to low initial stands, later stand losses, or plant defoliation has not been reported regarding replanting decisions and crop insurance yield loss assessment. Three experiments were conducted to study the affect of stand reduction, defoliation, and row spacing on dwarf sunflower yield and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Probably, aeration due to proper line sowing, easy interception of light and adequate reception of soil moisture and nutrients was the major advantage to the plants sown through drilling method over other seedling techniques. These results are in agreement with those of Johnson et al (2010) who concluded that drilling sown sunflowers resulted in greater head size and under this sowing technique the plants get optimally greater share of nutrients from the soil and utilize natural resources from the environment. The increasing planting density caused increased plant population, more competition among plants to grow vigorously, while under 30 cm plant spacing due to lowest plant population, the plants experienced better utilization of applied inputs and natural resources.…”
Section: Head Diameter (Cm)supporting
confidence: 92%
See 1 more Smart Citation
“…Probably, aeration due to proper line sowing, easy interception of light and adequate reception of soil moisture and nutrients was the major advantage to the plants sown through drilling method over other seedling techniques. These results are in agreement with those of Johnson et al (2010) who concluded that drilling sown sunflowers resulted in greater head size and under this sowing technique the plants get optimally greater share of nutrients from the soil and utilize natural resources from the environment. The increasing planting density caused increased plant population, more competition among plants to grow vigorously, while under 30 cm plant spacing due to lowest plant population, the plants experienced better utilization of applied inputs and natural resources.…”
Section: Head Diameter (Cm)supporting
confidence: 92%
“…Shariti and Amin (2003) found that with increasing planting density, the allocated share of the average plant for nutrients, other inputs and natural resources. Johnson et al (2010) and Pereira, & Hall (2019) reported that the thicker stems in sunflower ensure the plants to establish bigger seed head to produce more seed rows. Similarly, FeSO4 application resulted in encouraging results in regards to stem thickness, because there is interrelationship of stem thickness with the yield contributing traits.…”
Section: Plant Height (Cm)mentioning
confidence: 99%
“…A number of studies have been undertaken using mechanical defoliation as a substitute for insect or animal herbivory, disease, environmental extremes or other mechanical damage on plants as diverse as sunflowers (Johnson, 2003) and butternut squash (Rangarajan et al , 2003). The technique has been widely applied to experiments with trees, such as aspen (Hogg et al , 2002), oak (Li & Ma, 2003) and mountain birch (Anttonen et al , 2002) as well as in species with needles such as Scots pine (Honkanen & Haukioja, 1994) and white spruce (Piene, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The performances of tall, semi-dwarf and dwarf sunflower hybrids are different at various plant populations. The reduced-height sunflower hybrids responded better to high plant populations than the standard and tall hybrids did (Stanojević, 1989;Vannozi and Baldini, 1990;Feoli, 1993;Fick et al, 1985;Johnson, 2002).…”
Section: Introductionmentioning
confidence: 99%